Pengaruh Sukuk, Saham Syariah dan Reksadana Syariah terhadap Pertumbuhan Ekonomi Nasional Tahun 2018-2023 - Naylul Kirom; Ani Faujiah (Universitas 45 Surabaya, 2024)
In economic life, until now economic growth is a very important thing for a country. Not only Indonesia, but countries all over the world. In determining a development achievement in countries, it can be seen from the economic growth figures of each country. The quality of good or bad government policies can be seen and measured from the speed of national output growth. Indonesia is listed as one of the developing countries that requires a lot of capital to increase economic development, the Indonesian state is by growing the investment sector using capital market instruments. The formulation of the research problem is whether there is an influence between sukuk, sharia shares, sharia mutual funds on national economic growth. This research is quantitative research. The data used is secondary data. The data analysis technique used is multiple linear regression, and for data processing using the IBM SPSS version 23 program. The results of this research are 1. Sukuk (X1) have a positive and significant effect on national economic growth. 2. Sharia shares (X2) have a positive and significant effect on national economic growth. 3. Sharia mutual funds (X3) have a positive and significant effect on national economic growth. And together (simultaneously) the variables sukuk, sharia shares and sharia mutual funds have a positive and significant effect on national economic growth.